1998
DOI: 10.1136/jech.52.7.468
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cataract operations in Finnish male smokers unaffected by alpha tocopherol or beta carotene supplements

Abstract: Objective-To examine the eVect of tocopherol and carotene supplementation on the incidence of age related cataract extraction. Setting-The Conclusion-Supplementation withtocopherol or carotene does not aVect the incidence of cataract extractions among male smokers. (J Epidemiol Community Health 1998;52:468-472) Animal studies have shown that deprivation or overprovision of certain vitamins and micronutrients can aVect the development of cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 24 publications
(17 reference statements)
0
35
0
Order By: Relevance
“…[9][10][11] There has been considerable interest in the possible protective role of dietary antioxidants and supplements in age-related cataract, but evidence of effectiveness to date is equivocal. 3 In 2 clinical trials, high-dose antioxidant supplementation did not delay cataract formation, 12,13 but in a third study, supplementation did delay progression. 14 Tobacco smoking is a major modifiable risk factor for many chronic diseases.…”
Section: J Cataract Refract Surg 2005; 31:2395-2404 Q 2005 Ascrs and mentioning
confidence: 99%
“…[9][10][11] There has been considerable interest in the possible protective role of dietary antioxidants and supplements in age-related cataract, but evidence of effectiveness to date is equivocal. 3 In 2 clinical trials, high-dose antioxidant supplementation did not delay cataract formation, 12,13 but in a third study, supplementation did delay progression. 14 Tobacco smoking is a major modifiable risk factor for many chronic diseases.…”
Section: J Cataract Refract Surg 2005; 31:2395-2404 Q 2005 Ascrs and mentioning
confidence: 99%
“…Seven trials testing high-dose vitamin E supplements, either alone or in combination with other vitamin supplements, in generally well-nourished populations have found little benefit on cataract for treatment durations as long as 8 years in men and 10 years in women. 2228 For selenium, randomized trial data are limited. Selenium was included in a multivitamin/mineral combination found to be associated with a lower risk of cataract in a nutritionally-deficient population in China, 23 and in well-nourished populations in Italy 29 and the United States.…”
mentioning
confidence: 99%
“…7 10-45 Although the majority of epidemiological studies have shown a positive correlation between higher dietary antioxidant intake and decreased cataract formation, 7 11-27 conflicting conclusions exist. [36][37][38][39][40][41][42][43] Also, as studies on b carotene and lung cancer have shown, epidemiological evidence does not guarantee positive findings in interventional studies. [46][47][48][49] This is a report of the results of the Antioxidants in Prevention of Cataract (APC) Study, an interventional trial conducted in south India.…”
mentioning
confidence: 99%